Analisis Yuridis Pencantuman Klausul Force Majeure dalam Perjanjian Sewa Menyewa dan Pengelolaan Hak Milik Atas Satuan Rumah Susun Untuk Meneguhkan Kepastian Hukum (Studi Penelitian Di Kota Batam) - Kirtan, Tivonli; Respationo, Soerya; Erniyanti, Erniyanti; Fadlan, Fadlan (UNES Law Review, 2023)
A rental agreement is a mutual agreement that creates rights and responsibilities fot the parties involved in the agreement. Rental activities for apartment units in Batam City are often conducted verbally or through informal written agreement and ingnoring the inclusion of force majeure clauses so that there is no legal certainty for the parties. The research method used in this study is a combination of normative research and empirical research, which involves primary data through interviews and then correlating it with secondary data, such as statutory regulations and theories used in the study. The research findings indicate that there is Article 45 of Law Number 20 of 2011 which regulates the occupation of apartment units through written agreements made in the presence of authorizes officials and also Article 28 of the Government Regulation of the Republic of Indonesia Number 14 of 2016 concerning Imprementation of Housing and Settlement Areas addresses the inclusion of force majeure clauses. However, these provisions are often overlooked due to factors such as knowledge, age, social factors, and economic circumstances that influence people’s daily decision-making.